Comparison of oncological outcomes of right-sided colon cancer versus left-sided colon cancer after curative resection: Which side is better outcome?. Issue 42 (October 2017) - Lim, Dae Ro; Kuk, Jung Kul; Kim, Taehyung; Shin, Eung Jin
Abstract: Propose: There are embryological origins, anatomical, histological, genetic, and immunological differences between right-sided colon cancer (RCC) and left-sided colon cancer (LCC). Many studies have sought to determine the survival and prognosis according to tumor location. This study aimed to analyze outcomes between RCC and LCC. Material and method: Between January 2000 and December 2012, data on 414 patients who underwent curative resection for RCC and LCC were retrieved from a retrospective database. Propensity score matching (1:1) was performed and RCC was identified in 207 and LCC in 207 patients. Results: On average, RCC exhibited a more advanced N stage, increased tumor size, more frequently poorly differentiated tumors, more harvested lymph nodes, and more positivity of lymphovascular invasion than LCC. With a median follow-up of 66.7 months, the 5-year overall survival (OS) rates for RCC and LCC were 82.1% and 88.7%, respectively, ( P  < .05). The 5-year disease-free survival (DFS) rates were 81.4% (RCC) and 88.3% (LCC; P  < .05). In stage III cancers, the DFS rates were 61.1% (RCC) and 81.9% (LCC; P  < .05), while the OS rates were 65.6% (RCC) and 78.6% (LCC; P  = .056). Conclusion: On the basis of present data, LCC exhibited better survival outcomes than RCC after curative resection. Especially in stage III, LCC showed better oncologic outcomes. Proper specialized treatment related to the location of colon cancer is needed.